2018
DOI: 10.1111/acps.12899
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in unipolar depression preceding and following chronic somatic diseases

Abstract: A particularly high mortality risk was observed in the presence of prior depression for most somatic diseases. Future studies that assess the underlying mechanisms are necessary to adequately address the excessive mortality associated with comorbid depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Patients with psychiatric disorders tend to be nonadherent to treatment because of poor reasoning and lack of insight regarding their illness and therapy. Moreover, preexisting psychiatric disorders may result in the delayed detection of physical diseases until an advanced stage, when prognosis is poor [ 7 , 8 ]. Mounting evidence suggests that anxiety or depression are associated with aging-associated physical illnesses and worsening treatment outcomes are increasing [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psychiatric disorders tend to be nonadherent to treatment because of poor reasoning and lack of insight regarding their illness and therapy. Moreover, preexisting psychiatric disorders may result in the delayed detection of physical diseases until an advanced stage, when prognosis is poor [ 7 , 8 ]. Mounting evidence suggests that anxiety or depression are associated with aging-associated physical illnesses and worsening treatment outcomes are increasing [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the association between MD and mental distress, we also found that older people, women, smokers and subjects with one or more chronic diseases had higher mental distress and hence worse mental health. Poor physical health is often present in people with mental illness, increasing their mortality risk (Koyanagi et al , 2018). This is the reason behind the need for clinical integration of both pharmacological and nutritional intervention in caring for people with mental illness, especially those with comorbidities (Teasdale et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The latter have important clinical implications since depression may dramatically contribute to worsen those diseases and in general have an impact on overall health [164]. Indeed, comorbid depression has been associated with worse prognosis and increased mortality [165,166] and with a higher risk of developing other diseases later in life [167]. Several mechanisms have been proposed to explain the co-occurrence of depression with the comorbidities mentioned above, including treatment-induced morbidity, behavioral and psychological factors, but also underlying biological processes [163].…”
Section: Mdd Comorbidities and Plateletsmentioning
confidence: 99%